2021
DOI: 10.3390/ijms22116110
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyphenols in Metabolic Syndrome: Protective Mechanisms and Clinical Applications

Abstract: Metabolic syndrome (MetS) is a chronic disease, including abdominal obesity, dyslipidemia, hyperglycemia, and hypertension. It should be noted that the occurrence of MetS is closely related to oxidative stress-induced mitochondrial dysfunction, ectopic fat accumulation, and the impairment of the antioxidant system, which in turn further aggravates the intracellular oxidative imbalance and inflammatory response. As enriched anti-inflammatory and antioxidant components in plants, natural polyphenols exhibit bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 271 publications
(340 reference statements)
1
33
0
2
Order By: Relevance
“…The human body has many defense mechanisms that neutralize the harmful effects of reactive oxygen species. Antioxidants play an important role in reducing oxidative damage in the human body [1][2][3][4][5]. These are compounds which, even at a very low concentration, compared to the substrate, can delay or prevent its oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The human body has many defense mechanisms that neutralize the harmful effects of reactive oxygen species. Antioxidants play an important role in reducing oxidative damage in the human body [1][2][3][4][5]. These are compounds which, even at a very low concentration, compared to the substrate, can delay or prevent its oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Among all flavonoids, flavonols and flavones are the largest subgroups of polyphenols, and are the main components of flavonoids. 22 Modern pharmacological studies found that flavonoids could improve the body's antioxidant and free radical scavenging. Therefore, they are powerful antioxidants.…”
Section: Pharmacological Activities and Mechanisms Of Flavonoids Agai...mentioning
confidence: 99%
“…Non-flavonoids are represented by phenolic acids, which typically have two distinct parent skeletons, including hydroxycinnamic acid and hydroxybenzoic acid. 22,91 Although there are not as many types and compounds of nonflavonoids as flavonoids, many compounds of non-flavonoids have shown better anti-metabolic syndrome effects, such as gallic acid, resveratrol, punicalagin and so on.…”
Section: Pharmacological Actions and Mechanisms Of Non-flavonoids In ...mentioning
confidence: 99%
“…It has been observed that particularly flavonoids such as flavonols (myricetin) and anthocyanins, decrease biochemical parameters related to MetS, such as hypercholesterolemia, obesity, inflammation, and diabetes, this in clinical studies, in addition to delaying the pathogenesis of comorbidities such as Non-alcoholic fatty liver disease (NAFLD), and inhibit inflammatory cytokines, helping to reduce cardiovascular events, this due to the antioxidant activity of flavonoids, thanks to the hydroxyl groups present; therefore these compounds are of high bioactive importance for human health due to their safety and efficacy (Zhang, Xu, Zhang, Liu & Chen, 2021;Ginwala, Bhavsar, Chigbu, Jain & Khan, 2019).…”
Section: Biological Activities Of C Icacomentioning
confidence: 99%